Impact of elevated temperature on the properties of concretes reinforced with Alfa fiber - Mihoub, Imane; Khelifa, Mohammed-Rissel; Mezhoud, Samy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Alfa fiber reinforced concretes are not used to their full potential due to the limited information on their properties, especially in more severe environments. In this study, the effects of elevated temperature on the properties of concretes reinforced with Alfa fiber were analyzed. The influence of fiber length on reinforced concretes is mainly investigated.
Keywords: reinforced concrete; Alfa fiber; polypropylene fibre; temperature; sustainability; fiber length; beton zbrojony; włókno Alfa; włókno polipropylenowe; temperatura; rozwój zrównoważony; długość włókien